PSYCHOPHYSIOLOGIC AND IMMUNOLOGIC CHARACTERISTICS IN PATIENTS WITH BRONCHIAL ASTHMA AND HEALTHY MEN WITH DIFFERENT FUNCTIONAL ASYMMETRY OF BRAIN HEMISPHERES - T. Ya. Abramova (SPb RAACI, 2014)
Abstract. Possible interactions between psychophysiological and immunological parameters are documented in healthy persons and bronchial asthma patients, as based on our own data and other sources. A role of functional asymmetry of brain is regarded as a basic phenomenon determining main features of psychical activity, as well as functions of autonomous nervous system and immunological activity.